PENERAPAN MODEL PEMBELAJARAN PBL BERBANTUAN PUZZLE UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA SISWA SDN 1 JEMOWO - Purnomo, David Eko; Astuti, Suhandi (JURNAL MathEdu (Mathematic Education Journal), 2025)
This research aims to improve students' critical thinking skills and learning outcomes by applying the puzzle-assisted Problem Based Learning (PBL) learning model in grade 5 Mathematics learning. This type of research is Classroom Action Research (PTK). The subjects of this research were grade 5 students at SDN 1 Jemowo. Data collection techniques use pretest and posttest essay tests by integrating critical thinking skills. This research uses qualitative and quantitative descriptive data analysis techniques. The results of this research show an increase in critical thinking skills and learning outcomes of grade 5 students at SDN 1 Jemowo after implementing the puzzle-assisted Problem Based Learning (PBL) learning model. This is proven by an increase in students' critical thinking skills, namely in the first cycle pretest the average critical thinking skills of students was only 50.67. Furthermore, there was an increase in the first cycle posttest to 70.61. In the second cycle pretest, the average critical thinking skills of students was only 56.21, again increasing in the second cycle posttest to 75.66. Apart from that, student learning outcomes also increased from the first cycle pretest, the average student learning outcomes were only 58.24 to 73.59 in the first cycle posttest. The average student learning outcomes increased again from the second cycle pretest, 68.07 to 82.45 in the second cycle posttest. The students' learning completeness in the first cycle posttest results increased to 11 students (57.90%) completed and 8 students (42.10%) did not complete. Then, in the second cycle posttest, learning completion increased again to 18 students (94.74%) completed and 1 student (5.26%) did not complete.